Integration of Environmental Education in Eco Pesantren Daarut Tauhiid Bandung - Saprodi, Emtizal; Kastolani, Wanjat; Ningrum, Epon (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Environmental care is a characteristic that must be owned by everyone. For this reason, schools are required to develop an attitude of caring for the environment through curriculum and learning. The purpose of this study was to determine the integration of environmental education in eco-schools in Daarut Tauhiid Bandung, to find out the implementation of the eco boarding program in eco boarding schools, and to find out the evaluation of the integration of environmental education in eco boarding schools. The method used is descriptive. The research variables are environmental education, eco boarding program, environmental care attitude. The research instrument uses observation, interviews, and documentation. Data analysis uses descriptive. The research results show; integrating environmental education in eco boarding schools through three ways namely; first, the integration of environmental education through the national curriculum namely; human resource improvement, training, outreach, manuals, and programs. Integration through boarding school curriculum namely; Clean, Neat, Orderly and Organized Program (BRTT) and Clean, Green and Flowering (Berhiber) Program. Integrating environmental education through learning. Based on this, the researcher recommends that the implementation of environmental education and eco boarding school programs in schools can touch with balanced the cognitive, affective and psychomotor aspects of students.